Limites da arbitragem - Menna, Fabio de Vasconcellos (2010)
This dissertation intends to analyze the conflict resolution way called Arbitration, due to the need of intensifying the application of the devices foreseen in the Law of Arbitration (Law nº. 9.307/96), that aim to limit the Arbitration procedures without removing what it has as fundamental, that is, the freedom of convention of the parts and the choice for the judgement form, by equality before law or legal right. A brief revision of literature concerning the history of the Arbitration is made, with focus in Brazil and in the juridical nature of that institute, approaching constitutional and arbitrable principles, in order to make possible the relationship among them, mainly with respect to the resulting crisis in the Judiciary. Based on the relationship among principles, themes as equality before law, matter of public order, autonomy of parts will before the due legal process and compulsory nature or not of the referee to adopt the linked summary. The mark of this work is seeking for a better understanding about the advantages of Arbitration, among them the decongestion of the Judiciary, and forms of guaranteeing to one that opted for that solving conflicts way the juridical safety